Code compliance checking of railway designs by integrating BIM, BPMN and DMN - Häußler, Marco; Esser, Sebastian; Borrmann, André (Automation in construction, 2021)
Code compliance checking has been the subject of scientific research for more than four decades and has been put into practice in numerous projects. To date, however, no universally valid, sustainable approach to the rule-based compliance checking of models has been established. Visual programming languages are easier to understand and thus more transparent than textual formats. The study presented here analyzes the requirements specified in the guidelines of the Deutsche Bahn AG regarding the technical design of structures in railway construction and examines the feasibility of implementing these rules using BPMN and DMN. The rules analyzed are categorized into 12 different classes. Depending on the guideline subset, the BPMN/DMN approach was found to be useable in 37%-75% of the 943 rules examined. Considering only those rules that are relevant for the digital railway model, 68% of the rules can be represented and automated using BPMN and DMN. •The big potential of quality assurance using BIM is currently not fully exploited.•The usage of BPMN and DMN in terms of Code Compliance Checking is presented.•The usability of BPMN and DMN while checking BIMs against guidelines of railway infrastructure is analyzed statistically.